Building a hybrid approach for a game scenario using a tangible interface in human robot interaction - Silva, Vinicius Corrêa Alves (2018)
Understanding others intention can be a very difficult task for some individuals, in particular, individuals with Autism Spectrum Disorder (ASD). ASD is characterized by difficulties in social communication and restricted patterns of behaviour. In order to mitigate the emotion recognition impairments that individuals with ASD usually present, researchers are employing different technological strategies. Among those technological solutions, the use of assistive robots and Objects based on Playware Technology (OPT) in context of serious games are getting more attention. Following this trend, the present work targets a novel hybrid approach using a humanoid robot and one OPT. The proposed approach consists of a humanoid robot capable of displaying social behaviours, particularly facial expressions, and an OPT called PlayCube. The system was designed for emotion recognition activities with children with ASD. To evaluate the proposed approach, two pilot studies were performed: one with typically developing children and another with children with ASD. Overall, the different evaluations demonstrated the possible positive outcomes that this child-OPT-robot interaction can produce.